Do US Firms Pay Less Tax than their European Peers? On Firm Characteristics, Profit Shifting Opportunities, and Tax Legislation as Determinants of Tax Differentials - Michael Overesch; Sabine Schenkelberg; Georg Wamser (Center for Economic Studies and ifo Institute (CESifo), 2018)
Using pairs of similar US and European firms listed on the S&P500 or StoxxEurope600, we examine effective tax differentials between US multinational corporations (MNCs) and their European peers. We show that statutory tax rates and profit shifting opportunities are important determinants of effective tax rates. Our findings suggest substantially lower total tax payments of US MNCs after the 2017 US tax reform. Based on past reforms of Controlled Foreign Company (CFC) rules and of the principle of worldwide taxation, we confirm that international tax legislation affects effective tax expenses. We also provide evidence for heterogeneity in firm responses: MNCs with profit shifting opportunities benefit most from more-lenient CFC rules.
Keywords: H26; H32; F23; 330; effective tax rate; tax avoidance; tax reform; CFC rule; international taxation; pair matching; difference-in-differences analysis